2020
DOI: 10.3390/su12187714
|View full text |Cite
|
Sign up to set email alerts
|

Can Green Building Promote Pro-Environmental Behaviours? The Psychological Model and Design Strategy

Abstract: A green building has a long lasting benefit through cultivating the occupants’ energy and resource-saving behaviours. To understand how green buildings can cultivate occupants’ pro-environment behaviours, the research applied the value–belief–norm model to investigate 17 pro-environmental behaviours which are related to a variety of green building design strategies. Two green and two non-green certified office buildings in the city of Shenzhen in China were surveyed, based on which structural equation modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Werff et al, ( 2014 ) found that customers’ perceptions of environmentally friendly products are strongly influenced by their perceptions of biospheric values. Green values often influence pro-environmental behaviour (Xie et al, 2020 ). It is also found that customers participate in ecological activities when their environmental feelings are strong (Meijers et al, 2019 ).…”
Section: Biospheric Valuementioning
confidence: 99%
“…Werff et al, ( 2014 ) found that customers’ perceptions of environmentally friendly products are strongly influenced by their perceptions of biospheric values. Green values often influence pro-environmental behaviour (Xie et al, 2020 ). It is also found that customers participate in ecological activities when their environmental feelings are strong (Meijers et al, 2019 ).…”
Section: Biospheric Valuementioning
confidence: 99%
“…When discussing various initiatives undertaken to educate employees, it is worth noting that Jackson and Seo [ 57 ] provided examples of companies that build employee gardens, thus stimulating employee gardening activities and, as a result, teaching employees what environmental sustainability means. Likewise, Xie et al [ 25 ] emphasized the importance of green office buildings in promoting PEB. In turn, Oppong-Tawiah et al [ 7 ] promote gamification.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…In recent years, with the popularity of social responsibility beyond economic concerns, more and more researchers discuss green risks from such a comprehensive perspective. corporate social responsibility (CSR), which requires corporations to follow the community regulations, adapt the local social value changes [95,96], attach importance to public opinion [97] and invest in environmentally friendly areas, becomes a key rule of corporate sustainability [33,34]. Branco and Rodrigues [34] discussed the internal and external advantages of taking CSR from a resource-based perspective.…”
Section: Internal Perception and Corporate Behaviormentioning
confidence: 99%